Meropenem/Vaborbactam, the First Carbapenem/β-Lactamase Inhibitor Combination. Issue 8 (August 2018) - Cho, Jonathan C.; Zmarlicka, Monika T.; Shaeer, Kristy M.; Pardo, Joe
Objective: To review the pharmacology, spectrum of activity, pharmacokinetics, pharmacodynamics, safety, efficacy, administration, and considerations for clinical use of meropenem/vaborbactam (M/V).Data Sources: A literature search using PubMed and clinicaltrials.gov (June 2013 to December 2017) was conducted using the search terms meropenem, vaborbactam, RPX7009, biapenem, RPX2003, and carbavance . References from relevant articles and conference abstracts were also reviewed.Study Selection and Data Extraction: Preclinical, phase I studies, and phase III studies written in the English language were evaluated.Data Synthesis: M/V is a novel carbapenem/β-lactamase inhibitor antimicrobial with in vitro activity against nearly 99% of Klebsiella pneumoniae carbapenemase–producing Enterobacteriaceae . M/V is approved for the treatment of adults with complicated urinary tract infections (cUTIs), including pyelonephritis. In a phase III cUTI trial (TANGO I), 98.4% of patients treated with M/V experienced overall clinical success compared with 94% of patients treated with piperacillin/tazobactam (95% CI = 0.7 to 9.1). When compared with best available therapy for carbapenem-resistant Enterobacteriaceae (CRE) infections in TANGO II, patients receiving M/V were more likely to achieve clinical cure at both the end of therapy (64.3% vs 33.3%, P = 0.04) as well as at the test of cure (57.1% vs 26.7%, P = 0.04). The most common adverse effects associated with M/V were headache, infusion-site reactions, and diarrhea.Conclusion: M/V has a valuable role in the treatment of CRE and should be used judiciously to preserve its use for resistant infections.